2012
DOI: 10.1016/j.cub.2011.11.058
|View full text |Cite
|
Sign up to set email alerts
|

An ARF6/Rab35 GTPase Cascade for Endocytic Recycling and Successful Cytokinesis

Abstract: Cytokinesis bridge instability leads to binucleated cells that can promote tumorigenesis in vivo. Membrane trafficking is crucial for animal cell cytokinesis, and several endocytic pathways regulated by distinct GTPases (Rab11, Rab21, Rab35, ARF6, RalA/B) contribute to the postfurrowing steps of cytokinesis. However, little is known about how these pathways are coordinated for successful cytokinesis. The Rab35 GTPase controls a fast endocytic recycling pathway and must be activated for SEPTIN cytoskeleton loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
157
2
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 149 publications
(171 citation statements)
references
References 34 publications
11
157
2
1
Order By: Relevance
“…In our preliminary experiments, the Rab35 SR (T76S/T81A) mutant was unable to rescue the multinucleation phenotype of HeLaS3 cells induced by Rab35 siRNA (15). 3 Because Arf6 is also known to be required for cytokinesis (16), there is a strong possibility that centaurin-␤2-mediated functional cross-talk between Rab35 and Arf6 occurs in cytokinesis. Investigation of the possible functional involvement of centaurin-␤2 in cytokinesis is now underway in our laboratory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our preliminary experiments, the Rab35 SR (T76S/T81A) mutant was unable to rescue the multinucleation phenotype of HeLaS3 cells induced by Rab35 siRNA (15). 3 Because Arf6 is also known to be required for cytokinesis (16), there is a strong possibility that centaurin-␤2-mediated functional cross-talk between Rab35 and Arf6 occurs in cytokinesis. Investigation of the possible functional involvement of centaurin-␤2 in cytokinesis is now underway in our laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…Rab35 is one such Rab protein and has been shown to bind various candidate effector molecules, including MICAL-1 (7), MICAL-L1 (7,9,10), MICAL-cl (7), OCRL (7,11), RUSC2 (12), Fascin1 (13), and centaurin-␤2 (8,14), and to be involved in various cellular events, including cytokinesis (11,15,16), cell migration (17,18), phagocytosis (19,20), immunological synapse formation (21), myelination (22), and neurite outgrowth (10,14,23,24), most likely through regulation of endocytic recycling (25). The pleiotropic roles of Rab35 in membrane trafficking may be attributable to the presence of multiple Rab35 effectors, but the involvement of individual Rab35 effectors in the above cellular events has remained largely unknown.…”
mentioning
confidence: 99%
“…In HeLa cells, Chesneau et al (38) showed that Arf6-GTP can interact with Rab35 GAP EPI64B, negatively regulating Rab35 activity during cytokinesis. Together with our results, these observations provide compelling evidence that Rab-to-Arf and Arf-to-Rab regulatory loops represent a general mechanism for the coordinate regulation of Rabs and Arfs during membrane trafficking.…”
Section: Discussionmentioning
confidence: 99%
“…In cultured human cells, Arf6(GTP) can interact with the Rab35 GAP EPI64B, negatively regulating Rab35 activity. 32 This work indicates that Arf6-to-Rab35 regulation is required for endocytic pathways important for cytokinesis. Taken together, the discoveries of Rab-to-Arf and Arf-to-Rab regulatory cascades suggest that signaling between these classes of small GTPases represent an evolutionally conserved mechanism that coordinates remodeling capability.…”
Section: Disclosure Of Potential Conflicts Of Interestmentioning
confidence: 99%
“…15,[30][31][32] Our studies provide an example of a Rab-toArf regulatory cascade, with RAB-10 and ARF-6 acting in sequential steps to regulate endosomal PI(4,5)P2 levels, thus regulating endosomal recruitment of PI(4,5)P2-binding proteins implicated in membrane bending and membrane fission. In addition to the Rab-to-Arf regulatory loops, an Arf-to-Rab regulatory cascade has also been recently reported.…”
Section: Disclosure Of Potential Conflicts Of Interestmentioning
confidence: 99%